2021
DOI: 10.1097/qad.0000000000002811
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of dyslipidemia in people with HIV who are treated with integrase inhibitors versus other antiretroviral agents

Abstract: Incidence of dyslipidemia in people with HIV who are treated with integrase inhibitors versus other antiretroviral agents The RESPOND Study Group M Objective: To compare the incidence of dyslipidemia in people with HIV receiving integrase inhibitors (INSTI) versus boosted protease inhibitors (PI/b) and nonnucleoside reverse transcriptase inhibitors (NNRTI) within RESPOND consortium of prospective cohorts. Methods: Participants were eligible if they were at least 18 years, without dyslipidemia and initiated or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…There were some concerns regarding switching of backbone drugs in the literature; PLWH who switched from a TDF-based to a TAFbased cART regimen showed increased low-density lipoprotein (LDL) values exceeding their cardiovascular risk targets. 18,19 In the present study, equally low switch rates were observed at one year for TAF, ABC, and TDF. However, the true impact of TAF on lipid pro les or cardiovascular risk was not evaluated and requires further study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…There were some concerns regarding switching of backbone drugs in the literature; PLWH who switched from a TDF-based to a TAFbased cART regimen showed increased low-density lipoprotein (LDL) values exceeding their cardiovascular risk targets. 18,19 In the present study, equally low switch rates were observed at one year for TAF, ABC, and TDF. However, the true impact of TAF on lipid pro les or cardiovascular risk was not evaluated and requires further study.…”
Section: Discussionsupporting
confidence: 54%
“…Of all patients who started an ART regimen from 2011 to 2019, 19 1). No signi cant differences were found in patients' characteristics between those treated with these three predominant anchor drug classes.…”
Section: Characteristics Of Patients Who Switched Anchor Drug Classesmentioning
confidence: 99%
“…In addition, in recent years there are increasing number of new formulations containing INTIs being released. There were some concerns regarding switching of backbone drugs in the literature; PLWH who switched from a TDF-based to a TAF-based cART regimen showed increased low-density lipoprotein (LDL) values exceeding their cardiovascular risk targets 18 , 19 . In the present study, equally low switch rates were observed at 1 year for TAF, ABC, and TDF.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study investigating the incidence of dyslipidemia in PLWH reported that older non-nucleoside reverse transcriptase inhibitors (NNRTIs), such as efavirenz and ritonavir-boosted protease inhibitors (PIs) containing ARTs, were associated with a greater risk of dyslipidemia than newer agents from the same class of ART. In addition, dyslipidemia was less common with INSTIs than with boosted PIs [ 32 ]. This report also found that, compared with dolutegravir, dyslipidemia was more common with elvitegravir/cobicistat and raltegravir but less common with rilpivirine.…”
Section: Dyslipidemia and Artmentioning
confidence: 99%